Global Antisemitism: A Crisis of Modernity - Asher Small, Charles (Brill, 2013)
This volume contains a selection of essays based on papers presented at a conference organized at Yale University and hosted by the Yale Initiative for the Interdisciplinary Study of Antisemitism (YIISA) and the International Association for the Study of Antisemitism (IASA), entitled "Global Antisemitism: A Crisis of Modernity." The essays are written by scholars from a wide array of disciplines, intellectual backgrounds, and perspectives, and address the conference's two inter-related areas of focus: global antisemitism and the crisis of modernity currently affecting the core elements of Western society and civilization.